Sustainable Tourism through the Tri Hita Karana Concept - Subrata, Kadek Diana Agustini Putri; Triyuni, Ni Nyoman; Septevany, Elvira (Centre For Tourism Planning and Development, 2025)
This study examines how the implementation of the Tri Hita Karana (THK) concept can support sustainable tourism. The participants for this study were selected using a purposive sampling technique. Data collection was conducted through observations and interviews. The data analysis method employed qualitative research techniques, including transcription, data reduction, data presentation, and drawing conclusions. The results of this study reveal that Anantara Uluwatu Bali Resort has successfully implemented the THK concept, as evidenced by the fulfillment of all indicators related to Parhyangan, Pawongan, and Palemahan. However, several indicators within the Pawongan and Palemahan aspects have not been fully optimized. These include the relationship between internal employees and management within the hotel, as well as the company's involvement in environmental conservation efforts. Based on these findings, this research suggests that further development of the Pawongan (human) and Palemahan (environmental) aspects is necessary to support sustainable economic, social, cultural, and environmental tourism.